Overcoming anxiety in English speaking - Sharipova, Bahora Odiljonovna; Norquvatova, Zarina (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This essay discusses the problem of speaking anxiety among English learners. It explains the main causes, such as fear of mistakes, lack of practice, and low self-esteem. The essay also describes the psychological effects of anxiety, including nervousness and loss of confidence. Several effective strategies are suggested to overcome this fear, such as developing a positive mindset, practicing regularly, and using relaxation techniques. The role of teachers and a supportive environment is emphasized as key to helping learners build confidence and improve fluency.